A bibliometric study of digital humanities research in China from 2012 to 2021 - Fangli Su; Shihao Li; Qinghua Liu; Yin Zhang (Information Research: An International Electronic Journal)
Introduction. We investigated the main research topics of digital humanities in China from 2012 to 2021, as well as the journals, authors, and institutions that produced the most research in this field.